Pembelajaran Digital Era Society 5.0: Pemanfaatan Quizizz dalam Meningkatkan Hasil Belajar Siswa - Siti Khumairah Fiqrilah; M. Rusydi Ridha; Dela Kartika Sari; Nur Fadilah dr; Samratan (Yayasan Al-Afif, 2025)
The purpose of this study was to determine how the use of Quizizz learning media affects student learning outcomes in review material in class XI at MA DDI Majene. The method used is Classroom Action Research (CAR) carried out in two cycles: planning, implementation, observation, and reflection. The subjects of the study were ten students in class XI during the first semester of the 2024/2025 academic year. Data were collected through learning outcome tests, observation, and documentation. The results showed that the application of the model improved student learning outcomes. game-based learning (Game Based Learning) using Quizizz. In the pre-cycle stage, the average student score was 62.4, with only 20% of students achieving the Minimum Completion Criteria (KKM). The average score increased to 82.8 after cycle I, with 60% of students achieving KKM. In cycle II, all students (one hundred percent) achieved scores above KKM. with an average score of 89.6. The application of Quizizz has been shown to significantly increase student participation, motivation, and learning outcomes. Thus, game learning media such as Quizizz are very effective in improving student learning outcomes in review material.